Análise diferencial dos padrões de habilidades visomotoras em alunos com atrasos acentuados de alfabetização - Lima, Rosa de Fátima Torres (1984)
This research aimed to analyze the differential performance visomotoras, verbal and non-verbal tasks, students late in literacy, classified according to different causal factors, based on the existence of advance neuropathological. They were taken as a proposed 84 children of both sexes, aged 9-15 years. These children were divided into three groups (two experimental and one control) and subjected to a battery of tests visomotoras skills, verbal and non - verbal. The results showed no significant differences in performance between groups of children with learning disorders. With or without traumatic history in most tasks, contrary to that, that the estimates of many researchers specifically, in this case, the assumptions Bannatyne (1971) for differential analysis of performance in these tests by children without neurological antecedents. However, if observed through evaluations, remarkable performance differences between the groups of children considered without learning problems and those problems. It was found also that some tests have shown a greater discriminatory power than others. In conclusion, despite some counter predictions Bannatyme and especially the assumptions that support a lower performance for children with learning problems, with a history with neuropathological dysfunction history, in verbal visomotoras tasks and non - verbal. There is also the feasibility of using some of these measures in the students classification with learning disorders.